ULTRASOUND-ASSISTED EXTRACTION OF INULIN-TYPE CARBOHYDRATES FROM Musa acuminata - Antari, Gladeva Yugi; Aini, Diah Miftahul; Malika, Riwayati (Indonesian Journal of Pure and Applied Chemistry, 2026)
Bananas (Musa acuminata) are a plentiful and underutilized tropical resource that has the potential to serve as an alternative source of inulin-type carbohydrates. The main objective of this study was to assess the effectiveness of ultrasonication in improving the yield and quality of inulin-type carbohydrates extracted from banana biomass. The extracted products are used at 40 kHz and 50 W for 15 min at 70 °C. Then, the samples were characterized using Fourier Transform Infrared (FTIR) spectroscopy and carbohydrate content determination to confirm the presence of inulin-type structures. The results demonstrated that the ultrasonication extraction efficiency was 10.914% and 33.57% for moisture contents of 10.914% and 33.57%, respectively. Spectral analysis confirmed the presence of characteristic functional groups associated with fructan-based carbohydrates, indicating successful extraction. In conclusion, ultrasonic-assisted extraction is a promising technology for the efficient recovery of inulin-type carbohydrates from banana biomass. Prospects include process optimization at pilot scale, integration with microwave-assisted extraction, and evaluation of the functional and prebiotic properties of the extracted inulin for food and biomedical applications.